Impaired Cellular Energy Metabolism Contributes to Duck-Enteritis-Virus-Induced Autophagy via the AMPK–TSC2–MTOR Signaling Pathway - Yin, Haichang; Zhao, Lili; Li, Siqi; Xu, Lijing; Wang, Yiping; Chen, Hongyan (Frontiers in Cellular and Infection Microbiology, 2017)
Duck enteritis virus (DEV) is a large, complex double-stranded DNA virus that induces duck embryo fibroblast (DEF) cells autophagy, which is beneficial to its own replication, but the mechanism has not been described. In this study, we showed that impaired cell energy metabolism is involved in DEV-induced autophagy, whereby ATP synthesis is disrupted in cells after DEV infection, which causes metabolic stress and activation of autophagy. Methyl pyruvate (MP) inhibited conversion of LC3I to LC3II and accumulation of GFP-LC3, which could reverse the energy loss caused by DEV infection. Inhibition of DEV replication by MP confirmed the above view. We found that infection with DEV activated the metabolic regulator 5' AMP-activated kinase (AMPK) and inhibited activity of mechanistic target of rapamycin (mTOR). In the cases where AMPK expression was inhibited, the LC3-I conversion to LC3-II ratio was decreased, as was GFP-LC3 point and DEV replication; in addition, inhibition of p-mTOR showed a reverse trend. We also found that tuberous sclerosis (TSC) 2 was a key mediator between AMPK and mTOR through activation by phosphorylation. siRNA targeting TSC2 was transfected to reverse the inhibition of mTOR, and down-regulate autophagy level and DEV replication, but AMPK expression was not changed, while siRNA targeting AMPK inhibited activation of TSC2. In conclusion, our findings indicate that energy metabolism in cell damage induced by DEV contributes to autophagy via the AMPK–TSC2–MTOR signalling pathway, which provides a new perspective for DEV and host interactions.